Formation, characterization and electrocatalytic activity of layer-by-layer self-assembled films containing polyoxomolybdate over Au surfaces - Volker, Edgar (2012)
We describe a novel strategy for the controlled fabrication of well-defined multilayer films incorporating a polyoxomolybdate anion (PMo12 O3À , POM) via ion exchange on Au electrodes. Composite films were 40 thoroughly characterized by ellipsometry, X-ray photoelectron spectroscopy (XPS), FTIR-ATR, quartz crystal microbalance (QCM) and cyclic voltammetry (CV). XPS and FTIR-ATR measurements showed that the Keggin structure of polyoxomolybdates is maintained as they are incorporated into the film. QCM experiments demonstrated that larger amounts of POM are incorporated into thicker film electrodes. EQCM and XPS measurements further showed that part of the film is delaminated when the modified electrodes were submerged in acid or basic solutions, but after this initial loss of mass the electrodes remain stable in time and with electrochemical use. POM-modified electrodes showed a pH-dependent electrochemical behavior, with peak potentials shifting by À60 mV pHÀ1, characteristic of a 2e/2H+ redox process at room temperature. Furthermore, our results suggest that POM molecules in the film are not decomposed when the electrodes are immersed in solutions with pH = 4.8 a key finding as POM mole- cules in solution suffer from complete hydrolysis at this pH value. Finally, the performance of these POM-modified electrodes as electrocatalysts was assessed via the reduction of nitrite, chlorate and peroxodisulfate.